Judge Stone : a novel [large type] - Davis, Viola, 1965-; Patterson, James, 1947- (Little Brown and Company, 2026)
Viola Davis and James Patterson have written an incredible courtroom drama and created the most unforgettable character in years. All rise...for Judge Stone. The most respected citizen in Union Springs, Alabama (population 3,314), is Judge Mary Stone. She holds two responsibilities sacred: running her family farm and presiding over her courtroom. It's there she draws the most controversial case in the history of the South. Criminally, it's open-and-shut. Ethically, there is no middle ground. Essentially, it's a choice between life and death. No judge can satisfy everyone. It would be dangerous to try. But Judge Stone is willing to fight to bring justice to the people and place she loves.